The Problems of Online Learning on Students' Interest in Learning Mathematics - Salsa Agustina; Hamdan Sugilar; Abdurrahmansyah Abdurrahmansyah; Rizqy Dwi Amrina (Gunung Djati Conference Series, 2022)
This study aims to determine the problems in the online learning period towards students' interest in learning mathematics. The rapid spread of the COVID-19 virus has become a major threat to all countries, especially Indonesia. Face-to-face learning in schools has been replaced by online learning during this pandemic. This causes students' motivation in learning mathematics to be reduced during the online learning process. The method used in this research is literature review. Data collected by reading books and articles that are relevant to the problem to be studied. The results of this study indicate that students' problems with online learning are quite serious so that they affect student interest. During the online learning process, students find it difficult. And students also feel bored with monotonous online learning. So as a teacher can overcome these problems by designing an interesting and fun online learning environment.